2018
DOI: 10.17826/cumj.427253
|View full text |Cite
|
Sign up to set email alerts
|

İleri evre pelvik organ proplapsusu olan kadınlarda yaşam kalitesi ve cinsel yaşam

Abstract: ÖzPurpose: This study aims to evaluate women with pelvic organ prolapse in terms of the risk factors and identify the effects of pelvic organ prolapse on quality of life and sexual function. Materials and Methods: Target population of the study was women who applied to the gynecology polyclinics in a university hospital and maternity and children hospital. The study was completed with 110 control and 81 case group participants. The data were collected through Personal Identification Form, Pelvic Floor Distress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…4,5 Sexuality is a fundamental part of human life, and is an important parameter for health and QoL. 6 Thus, the current study sought to identify factors that affect sexual activity in women with PFD, and the impacts of QoL, according to sexual activity status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Sexuality is a fundamental part of human life, and is an important parameter for health and QoL. 6 Thus, the current study sought to identify factors that affect sexual activity in women with PFD, and the impacts of QoL, according to sexual activity status.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of UI type was based on clinical complaints, according to the standardization developed by the ICS. The condition was then classified according to the International Consultation on Incontinence Questionnaire -Short Form (ICIQ-SF) total score, as slight (1-5), moderate (6)(7)(8)(9)(10)(11)(12), severe (13)(14)(15)(16)(17)(18) or very severe (19)(20)(21). 11,12 Perineal sensitivity and anal reflex were tested to investigate the integrity of the motor component of the pudendal nerve: bulbocavernosus cough and anocutaneous reflexes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this study showed that menopausal women were significantly associated with poor quality of life. This finding is supported by studies conducted in Turkey [20]. This is due to the fact that as the women entered the menopausal stage, there were physiological changes resulting in menopausal symptoms and worsening of the prolapse, which is a double burden that worsens the quality of life [1].…”
Section: Discussionmentioning
confidence: 60%
“…In addition, the QoL of POP on women's health has not yet been recognized as a public health problem in many developing countries. This is because only a few studies have examined POP about the normal deterioration of general health-related QOL in the general population [9,20].…”
Section: Introductionmentioning
confidence: 99%